PARENTAL GUIDANCE ON MATHEMATICS LEARNING FOR LOWGRADES STUDENTS DURING THE COVID-19 PANDEMIC (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Elementary school students in low grades are classified as early childhood with strong sensitivity during theirdevelopment. This period expects parents to optimize guidance and provide appropriate direction for children's learningactivities. Based on mathematics importance in life, the subject’s skills need to be developed from an early stage throughproper guidance. Since the Covid-19 pandemic, all learning activities are carried out from home, therefore parents have abigger role in guiding the children. Parental guidance implementation is important for maximum learning achievement andsuccess. Therefore, this research’s objectives were to (1) provide an overview of mathematics learning guidanceimplementation in the low grades during the pandemic, and (2) knowing parents’ needs, constraints and obstacles in carryingout the learning process. The method used was descriptive analysis with quantitative and qualitative approaches. The datawere obtained through questionnaires, documentation and interviews. Also, the results showed that parental guidance inmathematics learning during the pandemic had not been implemented properly. Parents also experienced various obstacles inguiding the children.